Sovereign bonds, coskewness, and monetary policy regimes - Li, Yulin; Wald, John K.; Wang, Zijun (Journal of Financial Stability, 2020)
Consistent with flight-to-quality, the coskewness between developed market sovereign bonds and global equity markets can help explain bond returns. A coskewness factor, defined as the return difference between the most negative coskewness bond portfolio and the most positive coskewness bond portfolio, carries a statistically significant unit price of risk of 43.8 basis points per month. Decreases in coskewness are also significantly associated with declines in bond yields. Coskewness declines during recessions when interest rates become low. Moreover, countries with a monetary policy regime which explicitly targets monetary aggregates have lower coskewness.